Building knowledge from the epistemology of the South: the importance of training researchers in initial teacher training - Parada Ulloa, Marcos; Lárez Hernández, José Humberto; Vega-Gutiérrez, Óscar (Frontiers in Education, 2024)
This study aims to reflect on the importance of considering epistemologies of the South and research training as benchmarks in the initial teacher of educators in the Latin American context. In recent years, there has been a growing recognition of the need to diversify and decolonize knowledge production in education, especially in the Global South. The epistemology of the South provides a conceptual framework that challenges traditional Eurocentric perspectives and promotes alternative ways of knowing and understanding education.To achieve the research objective, a literature review was conducted focusing on key concepts such as Southern epistemology, researcher training, and initial teacher education. The review encompassed academic articles, books and relevant theoretical frameworks. Content analysis techniques were employed to critically examine the literature, identifying themes, theoretical perspectives, and implications for research training in Initial Teacher Education (ITE).The findings of this study suggest that the incorporation of the epistemology of the South into researcher training can have a transformative impact on the educational sector. By adopting ways of knowing and understanding, future researchers can develop a more nuanced and contextualized understanding of educational phenomena. This approach promotes critical thinking skills and encourages researchers to question dominant narratives and power structures in education.Additionally, the study highlights the importance of integrating research training into initial teacher education. By fostering the development and consolidation of research skills and a critical mindset in future teachers, it promotes their transformation into change agents within the Latin American educational system in which they operate. From this perspective, research-oriented teacher training programs empower educators to engage in evidence-based practices, contribute to educational research, and advocate for pedagogical approaches that respond to local contexts and social realities in which they act.This study underscores the need to integrate Southern epistemologies and research training within into initial teacher education. By doing so, we can nurture a new generation of educators with critical thinking skills capable of effecting significant societal changes. This research contributes to the This is a provisional file, not the final typeset article ongoing dialogue on the decolonization of education and promotes the development of inclusive and contextually relevant educational practices.